x^4 - 11x^2+18=0
(x-3)*(x+3)*(x^2-2)=0
x-3=0 x = 3
x+3=0 x=-3
x^2-2=0 x^2=2 x = корень 2 x = корень 2 x=-корень 2
x = 3
x = -3
x = корень 2
x = -корень 2
ВОТ ЭТО ПРАВИЛЬНО ИСПРАВИЛ!
пусть и , тогда
или <=>
<=> или => или <=> или или или
ответ: {}
x^4 - 11x^2+18=0
(x-3)*(x+3)*(x^2-2)=0
x-3=0 x = 3
x+3=0 x=-3
x^2-2=0 x^2=2 x = корень 2 x = корень 2 x=-корень 2
x = 3
x = -3
x = корень 2
x = -корень 2
ВОТ ЭТО ПРАВИЛЬНО ИСПРАВИЛ!
пусть
и
, тогда
<=>
или
=>
или
<=>
или
или
или ![(x=3)](/tpl/images/0048/4657/f5861.png)
ответ: {
}